1997
DOI: 10.1093/humrep/12.7.1494
|View full text |Cite
|
Sign up to set email alerts
|

Single versus double insemination: a retrospective audit of pregnancy rates with two treatment protocols in donor insemination

Abstract: Our objective was to evaluate the effect of a change in treatment protocols, suggested following an inspection visit by the regulatory authority, from single to double inseminations during donor insemination treatment cycles. We therefore conducted a retrospective audit of pregnancy rates in the reproductive medicine clinic of a major teaching hospital. All patients were treated for male factor infertility by donor insemination, without ovulation induction with gonadotrophins between October 1992 and December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The literature that addresses this specific question in donor sperm frozen‐thawed insemination cycles is limited and conflicting. A few studies using either natural cycles or ovarian stimulation showed benefit from double inseminations (Centola et al, 1990; Deary et al, 1997; Matilsky et al, 1998) and 1 study did not show any benefit (Khalifa et al, 1995). Two of these studies, however, compared single vs double ICIs (Centola et al, 1990; Deary et al, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The literature that addresses this specific question in donor sperm frozen‐thawed insemination cycles is limited and conflicting. A few studies using either natural cycles or ovarian stimulation showed benefit from double inseminations (Centola et al, 1990; Deary et al, 1997; Matilsky et al, 1998) and 1 study did not show any benefit (Khalifa et al, 1995). Two of these studies, however, compared single vs double ICIs (Centola et al, 1990; Deary et al, 1997).…”
mentioning
confidence: 99%
“…A few studies using either natural cycles or ovarian stimulation showed benefit from double inseminations (Centola et al, 1990; Deary et al, 1997; Matilsky et al, 1998) and 1 study did not show any benefit (Khalifa et al, 1995). Two of these studies, however, compared single vs double ICIs (Centola et al, 1990; Deary et al, 1997). One prospective study using frozen‐thawed donor sperm demonstrated a 2‐fold probability of conception over 15 cycles in patients who received double IUI (Matilsky et al, 1998).…”
mentioning
confidence: 99%
“…Table 2 summarizes the characteristics of a total of 54208 IUI cycles (excluding 32 cycles of lost visits) with 7773 clinical pregnancy outcomes in these 23 studies. Deary 1997 [19] (1992-1995) Hill 2013 [21] ( Monseur 2019 [24] (1999-2017) Guo Yu-rui 2016 [29] ( Yin Ming-na 2014 [30] ( Li Jing 2010 [32] ( Li Si-Chen 2016 [33] ( Li Hong-xia 2020 [34] ( Li Jing 2014 [35] (2012-2013) Wang Gang 2017 [37] ( Guo Jianghua 2007 [39] (…”
Section: Basic Characteristics Of the Included Literaturementioning
confidence: 99%
“…Importantly, most of the studies analyzed homologous IUI, however, some studies compared one versus two donor inseminations. The first articles are in favor of double insemination [88], including those where frozen-thawed donor sperm was used [89,90], while current studies are against double IUI, showing similar clinical pregnancy rates in both groups and proving no double IUI cycles are needed when donor sperm is used [91,92].…”
Section: Single Versus Double Intrauterine Inseminationmentioning
confidence: 99%